Kepribadian Ekstrovert dan Introvert pada Siswa Kelas VII G SMP Negeri 2 Ponorogo pada Proses Pembelajaran dalam Prespektif Psikologi Sosial - Widya Zulfa Ulwiyah; Muhammad Widda Djuhan (JIIPSI: Jurnal Ilmiah Ilmu Pengetahuan Sosial Indonesia, 2021)
Personality has a difference, namely Extrovert and Introvert. With the different personalities possessed by these students, of course, their reactions and interactions are also different when learning takes place. The purpose of this study was to determine how the social interaction of a student with an extroverted personality with an introverted personality student. When learning in the classroom is taking place, when using different learning methods in social studies learning. In this study, researchers used descriptive qualitative research methods that have natural characteristics and emphasize the process. Data was collected using observation, interview and documentation techniques. The technique of checking the validity of the data is done by time triangulation. The analysis technique uses the analysis of the Miles & Huberman model by using the steps of reducing data, presenting data, and drawing conclusions. The results showed that (1) there were differences in the interaction between extroverted and introverted personalities when using the social studies learning and learning method (2) for students with introverted personalities to be more suitable to use the discussion method, while extroverted personalities were able to adapt (3) social interactions were created well thus in accordance with social psychology in which they are able to behave, think, in the context of social situations.